INFLUENCE OF THE INDUCTION HEAT ON STRUCTURE FORMATION AT RECRYSTALLIZATION ANNEALING OF THE CIRCULAR ROLLED STEEL - P. S. Gurchenko; A. I. Mihluk (Литьë и металлургия)
There are studied the peculiarities of structure formation at crystallization expression using induction heat by currents with frequency 2400 and 8000 Hz of rod iron with diameter 16-40 mm from steels 35,40 and 40X. It is determined that single induction heat during 2-5 minutes provides required structure and solidity and reduction of the thermal cycle in comparison with furnace annealing (5-8 hours). There is developed the technology and equipment for recrystallization annealing with heating of TVCh of rod rolled metal at production of fixing articles of automobiles with outside threaded profile. There are developed the regimes of thermotreatment with induction heat of rolled metal at moving of rod material with diameter from 12 to 28 mm and length 6 m through multitum inductor with different speeds and parameters of heat.